Calculus : early transcendental functions / Robert T. Smith, Roland B. Minton - Smith, Robert T. (Robert Thomas) 1955- (McGraw-Hill Higher Education, 2007)
Smith/Minton's Calculus: Early Transcendental Functions, 3/e focuses on student comprehension of calculus. The authors' writing style is clear and understandable, reminiscent of a classroom lecture, which enables students to better grasp techniques and acquire content mastery. Modern applications in examples and exercises connect the calculus with relevant and interesting topics and situations. Detailed examples provide students with helpful guidance that emphasizes what is important and where common pitfalls occur. The exercise sets are balanced with routine, medium, and challenging problems. Technology is integrated throughout the text, but only where it makes sense. These elements all combine to provide a superior text from which students can read, understand, and very effectively learn calculus.